Neogene-quaternary seismic stratigraphy of the llancanelo lake basin, Mendoza, Argentina Estratigrafía sísmica neógeno-cuaternaria de la cuenca de la laguna de llancanelo, Mendoza, Argentina. - Onnis, Luciano Emanuel (2017)
A new shallow multichannel seismic survey was carried out in the Llancanelo Lake region (Southern Mendoza Province, Argentina), in order to complete and extend previously surveyed seismic sections. The new seismic data allowed to double the already existing data. The obtained information was correlated with seismic and stratigraphic data from the industry. In this way it was possible to depict the major Neogene-Quaternary sedimentary-volcanic sequences and the regional evolution of a tectonic-volcanic basin located in a key region at the eastern foot of the Andes cordillera. This research is settled on early studies that comprised seismic works reaching depths of 600-700 m as well as geoelectric and electromagnetic surveys reaching the uppermost 80-100 m of the sequences. The obtained results indicate the presence of three major sedimentary units separated by conspicuous seismic horizons SR1, SR2 and SR3, respectively considered as representing the late Mesozoic transition from marine to continental deposition, the beginning of the Cenozoic basaltic volcanism, and the change from dominantly sedimentary to dominantly volcanic processes at the base of the Quaternary. The resulting stratigraphic scheme reveals increasing volcanic (basaltic layers) intercalations with depth that accommodate to the geometry of the depocenter.